2016
DOI: 10.1108/s1746-979120160000012001
|View full text |Cite
|
Sign up to set email alerts
|

Abusive Supervision, Employee Well-Being and Ill-Being: The Moderating Role of Core Self-Evaluations

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 105 publications
(155 reference statements)
1
40
0
Order By: Relevance
“…(2003) [26], comprised of four axes of emotions, which ranges from pleasant to unpleasant emotions and high work activation to low work activation. This was done to indicate the intensity of psychological health conditions and the work activation levels of employees having these psychological conditions (O'Donoghue, et al, 2016) [11]. Psychology health conditions have also been categorised into five subgroups depending on the severity such as normal, mild, Occupational Diseases and Environmental Medicine moderate, severe and extreme levels (Millward, 2006;Offei and Quansah, 2009) [29] [30].…”
Section: Background Of Studymentioning
confidence: 99%
See 2 more Smart Citations
“…(2003) [26], comprised of four axes of emotions, which ranges from pleasant to unpleasant emotions and high work activation to low work activation. This was done to indicate the intensity of psychological health conditions and the work activation levels of employees having these psychological conditions (O'Donoghue, et al, 2016) [11]. Psychology health conditions have also been categorised into five subgroups depending on the severity such as normal, mild, Occupational Diseases and Environmental Medicine moderate, severe and extreme levels (Millward, 2006;Offei and Quansah, 2009) [29] [30].…”
Section: Background Of Studymentioning
confidence: 99%
“…The effects of burnout could also be manifested in the form of anxiety, fatigue, insomnia, depression, and impairment in work performance (Colman, 2003) [35]. Workers experiencing burnout can also be associated with work displeasure and low levels of work activation or motivation (O'Donoghue, et al, 2016; Fordjour and Chan, 2019) [11] [25]. Emotional exhaustion which is a characteristic of burnout is a psychological state with the victims lacking motivation or energy to work (Demerouti, et al, 2010) [36].…”
Section: Effects Of Burnout As An Occupational Psychological Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Psychology in the workplace stretches beyond the boundaries of the physical settings of the workplace [1]. Previous researchers revealed that psychological health conditions of employees such as stress, depression, anxiety, and frustration were influenced not only by exogenous events but also by factors that emanated from the workplace [2]. Factors that cannot be found in the work setting also influenced employees' behaviors and psychological health conditions [1].…”
Section: Introductionmentioning
confidence: 99%
“…These factors may include cultural, environmental influences, personality, family background, relationship responsibilities, employment-related requirements and non-working events [1] [3]. Other endogenous factors such as employees' perception or core beliefs also arouse the circumstances which led to an individual's experiences of psychological health conditions [2] [3]. It was revealed in a study by Mäkikanges et al [4] that, there was a positive relationship between personal factors of employees such as self-esteem and their occupational psychological health, specifically burnout and work engagement.…”
Section: Introductionmentioning
confidence: 99%